Biosorption of hexavalent chromium based on modified Y zeolites obtained by alkali-treatment - Figueiredo, Hugo (2010)
The structural modification of external surface of NaY was investigated in order to enhance efficient biosorption systems consisting of a bacterial biofilm, Arthrobacter viscosus, supported on that zeolite, for removing hexavalent chromium from aqueous solutions. The supported bacterial biofilm reduces Cr(VI) to Cr(III) and this cation is then retained in the zeolite by ion exchange. NaY zeolite was modified by alkali-treatments using NaOH 2.0 M, with two different contact periods of time between the zeolite and the alkaline solutions, resulting in NaYA and in NaYB. The biosorbents supported on the modified NaY zeolite were tested in solutions with low concentration of chromium. The results showed that the modification of external surface of NaY zeolite allows an efficient Cr removal, and the maximum removal efficiency was observed for NaYA sample that was submitted to a smoother chemical treatment.